Premorbid nutrition and short term outcome of stroke: a multicentre study from India. Issue 10 (22nd March 2011) - Pandian, Jeyaraj Durai; Jyotsna, Rashmi; Singh, Ruma; Sylaja, Padmavati N; Vijaya, Pamidimukkala; Padma, Madakasira Vasantha; Venkateswaralu, Kolichana; Sukumaran, Sajith; Radhakrishnan, Kurupath; Sarma, Prabhakaran S; Mathew, Robert; Singh, Yashpal
Abstract : Background: Little is known about the impact of premorbid undernutrition on stroke outcome in developing countries. Aim: To study the impact of premorbid undernutrition status, measured by the Subjective Global Assessment (SGA) tool, on short term stroke outcome. Methods: First ever stroke patients admitted to six major hospitals in North and South India participated in this study from 1 March 2008 to 30 September 2009. The SGA tool was administered within 48 h of stroke onset, and 6 months premorbid nutritional status was rated as well nourished (A rating) and undernourished (B and C ratings) using this tool. Stroke outcome was assessed after 30 days using the modified Rankin scale (mRs), and a mRs score >3 was defined as a poor outcome. Statistical analyses were performed using SPSS Statistics V.17.0. Results: Of 477 patients enrolled, 448 patients were included in the analyses. Mean age was 58.1±13.7 years (range 16–96) and 281 (62.7%) patients were men. At admission, premorbid undernutrition was found in 121 (27.2%) patients. Older age (OR 4.99, CI 1.26 to 19.64, p=0.021), hypertension (OR 1.99, CI 1.04 to 3.79, p=0.037) and patients from Andhra Pradesh State (OR 1.87, CI 1.05 to 3.32, p=0.032) were predictors of undernutrition in multiple logistic regression analysis. Premorbid undernutrition (OR 1.99, CI 1.20 to 3.31, p=0.007) and length of hospital stay (OR 3.41, CI 1.91 to 6.06, p<0.0001) were the independent predictors of poor outcome in the multiple logistic regression model. Conclusions: High rates of premorbid undernutrition in stroke patients were found. Age, hypertension and patients from Andhra Pradesh State were predictors of premorbid undernutrition. Premorbid undernutrition was associated with poor stroke outcome. The results provide opportunities for primary prevention and improving stroke outcome.